(untitled) (Research, Society and Development, 2020)
Creole beans have their own sensory attributes and are consumed mainly by family farmers. Within the species Vigna unguiculata, there is a group of varieties generically recognized as “soup”, which according to family farmers and quilombolas living in southern Brazil, have high nutritional and cultural value. In view of this, the objective was to formulate a gluten-free cake added with “soups” beans and evaluate its sensory characteristics in order to obtain a product with great acceptance from consumers and with positive sensory attributes. It was evaluated through the Acceptance Test with a 7-point hedonic scale (n = 50) and the Temporal Sensitivity Dominance test (n = 20). The test is applied using the SensoMaker software, in which the evaluators taste the samples within 30 seconds in order to perceive the most dominant attribute According to the results of the acceptance analysis, a relative frequency was obtained in the term “I liked it” a lot ”of 53.7% for the texture, 57.03% for the odor, 43.56% for the flavor and 48.47% for the overall impression, with no rejection by the evaluators. For DTS, it was observed that the sweet taste and softness were the most dominant attributes. It can be concluded that the gluten-free cake made with Creole beans was widely accepted by consumers, as well as having desirable sensory characteristics such as softness and sweetness, indicating the potential for making gluten-free cakes.